A study of the Oxidative stress and Antioxidant status in diabetic subjects who are on treatment with Metformin - Koshy, Manju; Jeeji, Palocaren; S, Sethupathy (International Journal of Clinical and Biomedical Research, 2019)
Background: Oxidative stress plays an important role in the pathogenesis of DM and its complications. However, antioxidant status and its contribution to type 2 DM are less explored in South Indian population. Metformin, is a biguanide anti hyperglycemic agent used for the management of type 2 diabetes. Aim:Â  To study the alteration in oxidant and antioxidant status in type 2 diabetic subjects on treatment with Metformin and to evaluate the effect of metformin in improving the total antioxidant status. Methodology: In this cross sectional study, all subjects were T2DM patients, on metformin monotherapy (500 mg, bd) and were grouped into two - Group 1 and Group 2 for the study purpose, based on their HbA1c values. Baseline parameters (B.P, Waist Hip ratio, BMI, family history), glycemic status, lipid profile, FRAP, TBARS and serum Metformin levels were assayed. Fasting and postprandial blood specimens were collected and plasma glucose concentrations were measured by standard methods. Fasting plasma total antioxidant capacity (TAC) was measured by ferric reducing ability of plasma (FRAP) assay. Oxidative stress was evaluated and measured as TBARS and the values were compared among the two groups. Results: TBARS levels were higher and FRAP levels were significantly lower in Group I subjects compared to Group II subjects and can be explained due to increased superoxide ions and reduced activity of S. O. D. Conclusion: It may be concluded that total antioxidant status is lower in type 2 diabetic subjects of Group 1 category compared to diabetic subjects in the Group 2 and it may be related to the beneficial effects of the biguanide, Metformin.